Mathematics at Ali bin Abi Talib (peace be upon him)- part two (Religious denar)- Mathematical encryption language of Ali bin Abi Talib in solving problems Mathematical, Philosophical, and Historical study - Al-Kufi, Mohammed Abdul Hameed Jassim; Al-Salihi, Hussein Abbas (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
After scientific research was completed by Muhammad al-Kufi looking into the subject of mathematics with Ali bin Abi Talib, peace be upon him, which was devoted to the topic of distributing 17 sentences to three people, one of them the half, the second the third, and the third nine, we decided, We decided, with the grace and success of God, to present a new study within the aspect of mathematics, history and Islamic philosophy, on an issue known historically as the Dinar Question. It is a question of inheritance. Ali bin Abi Talib, peace be upon him, gave a scientific opinion on this and he was very accurate in his opinion. As a woman came to Ali bin Abi Talib, and complained to him that her brother died and left 600 dinars, and she only got one dinar from his inheritance. He told her directly: Did your deceased brother leave a wife, two daughters, a mother, and twelve brothers and you? And she said yes. He said if your share of the inheritance is correct, and it is only one dinar. Here, the strength of his knowledge and intuition is evident. As soon as he knew its share, he deduced the number of family members, not only that, but the relationship between them, their gender, and the share of each of them. Since this woman was expecting her share more than that, she asked for equity. The explanation for this is: - He left two daughters with two-thirds, which is 400 dinars. A mother left her a sixth, which is 100 dinars. He left a wife with the price, which is 75 dinars. He left 12 brothers and sisters, each brother had two dinars, and she only had one dinar. This is the distribution of inheritance according to Islamic law, according to the sects of other than the Imamate Shiites. If we combined these shares, they would total 600 dinars, which is the total amount. Details about this issue will be contained within the articles of this research and in details, where we will detail the thought of Ali bin Abi Talib and how he was dealing with intractable issues that have a mathematical and non-mathematical aspect. We will also put forth philosophical opinions related to this topic and what some philosophers have said about Ali bin Abi Talib, and whether there are complaints about his decisions and treatments of the urgent issues brought before him. The case of the dinar question under discussion, which leads to the same share of the questioning woman. The most important part of this research is to analyse the issue mathematically and to find out the truth of the thinking of Ali bin Abi Talib, who used to develop solutions to such an issue by forming a mathematical model in his mind through which he derives solutions that are always accurate and as if he uses vital mathematics to give answers to the issues presented on him. Here is the complete search according to the details.